Morphisms of Mislin genera induced by finite normal subgroups - P. J. Hilton; P. J. Witbooi (International Journal of Mathematics and Mathematical Sciences)
We correct an erroneous statement about induced morphisms of Mislin genera and give the correct statement, even under more general hypotheses.